Generation of Transgene-Free Maize Male Sterile Lines Using the CRISPR/Cas9 System - Chen, Rongrong; Xu, Qilong; Liu, Yan; Zhang, Jiaojiao; Ren, Dongtao; Wang, Guoying; Liu, Yunjun (Frontiers in Plant Science, 2018)
Male sterility provides a useful breeding tool to harness hybrid vigor during hybrid seed production. It is necessary to generate new male sterile mutant materials for the development of hybrid seeds production technology. The CRISPR/Cas9 technology is well suited for targeting genomes to generate male sterile mutants. In this study, we artificially synthesized Streptococcus pyogenes Cas9 gene with biased codons of maize. A CRISPR/Cas9 vector targeting the MS8 gene of maize was constructed and transformed into maize using an Agrobacterium-mediated method, and eight T0 independent transgenic lines were generated. Sequencing results showed that MS8 genes in these T0 transgenic lines were not mutated. However, we detected mutations of MS8 in F1 and F2 progeny of transgenic line H17. A potential off-target site sequence which had a single nucleotide difference from the target was also mutated in the F2 progeny of transgenic line H17. Mutation of MS8 and the male sterile phenotype can be stably inherited in the next generation in a Mendelian fashion. Transgene-free ms8 male sterile plants were obtained by screening the F2 generation of male sterile plants, and the male sterility phenotype can be introduced into other elite inbred lines for hybrid production.